Emphatic Topicalization and the Structure of the Left Periphery: Evidence from German and Bangla. (3rd October 2016) - Bayer, Josef; Dasgupta, Probal
Abstract: The goal of this article is to explore the structure of the clausal "left periphery" with respect to a phenomenon that has so far only rarely been identified as a root‐clause phenomenon: emphatic topicalization (ET). It is a form of movement by which a phrase (not necessarily a wh ‐phrase) targets the specifier of a complementizer. This movement prevents the CP complement from remaining in its embedded position. For convergence, the entire CP in which ET has applied must move to the left periphery of the clause that immediately dominates it. It is argued that this latter move is necessary because ET induces a feature that is only interpretable in the domain of illocutionary force, illocutionary force being a property of the utterance (i.e., typically of the root clause). The data come from the Bavarian dialect of German (Germanic) and from Bangla (Indo‐Aryan). In spite of the differences between these languages, the similarity of the constraints that are revealed by this study cannot be accidental. For Bangla, a typical wh ‐in‐situ language, it is shown that the syntax of ET scope is to a large extent parallel to the syntax of wh ‐scope. Thus, the syntax of wh ‐scope can be argued to follow from general properties of the parametric choices made in Bangla (and perhaps in closely related languages).